2021
DOI: 10.3390/math9212710
|View full text |Cite
|
Sign up to set email alerts
|

Irregularity and Modular Irregularity Strength of Wheels

Abstract: It is easily observed that the vertices of a simple graph cannot have pairwise distinct degrees. This means that no simple graph of the order of at least two is, in this way, irregular. However, a multigraph can be irregular. Chartrand et al., in 1988, posed the following problem: in a loopless multigraph, how can one determine the fewest parallel edges required to ensure that all vertices have distinct degrees? This problem is known as the graph labeling problem and, for its solution, Chartrand et al. introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In 2021, Bača et al [4] characterized the modular irregularity strength of fan graphs F n for n ≥ 2. In the same year, Bača et al in [3] found the modular irregularity strength of wheels W n . Sugeng et al in [14] provided the results for the modular irregularity strength of double-stars S k,k and friendship graphs f n .…”
Section: Introductionmentioning
confidence: 90%
“…In 2021, Bača et al [4] characterized the modular irregularity strength of fan graphs F n for n ≥ 2. In the same year, Bača et al in [3] found the modular irregularity strength of wheels W n . Sugeng et al in [14] provided the results for the modular irregularity strength of double-stars S k,k and friendship graphs f n .…”
Section: Introductionmentioning
confidence: 90%
“…The modular irregularity strength for some graphs have known, such as path, star, tree, cycle, gear graph [4] , fan graph [3] , and wheel graph [1] . Recently, Sugeng, et al have determined the modular irregularity strength of double stars and friendship graphs [12] .…”
Section: Modular Irregular Labelling On Dodecahedral Modified General...mentioning
confidence: 99%
“…Considering Theorem 1, the interesting topic is the conditions for a graph 𝐺 such that 𝑠(𝐺) = 𝑚𝑠(𝐺) and 𝑠(𝐺) < 𝑚𝑠(𝐺). Bača et al in [29] compared the irregularity strength and modular irregularity strength of wheels. If 𝑛 = 5 or 𝑛 ≡ 1 (𝑚𝑜𝑑 4), then 𝑠(𝑊 𝑛 ) < 𝑚𝑠(𝑊 𝑛 ), otherwise 𝑠(𝑊 𝑛 ) = 𝑚𝑠(𝑊 𝑛 ).…”
Section: Introductionmentioning
confidence: 99%